EFEKTIVITAS PEMBERIAN VIDEOSCRIBE UNTUK KESIAPAN BELAJAR SISWA KELAS XI MATA PELAJARAN ESTIMASI BIAYA KONSTRUKSI DI SMK PU NEGERI BANDUNG - Winda Nurazizah; Sukadi Sukadi; Parmono Parmono (Universitas Pendidikan Indonesia (UPI), 2023)
Effective learning is usually characterized and measured by the level of achievement of goals by most students. To achieve learning success, it is necessary to have a readiness to learn. Learning with readiness is closely related, because learning without readiness will not get optimal results. But in reality what happened at SMK PU Negeri Bandung, class XI students were not ready to learn, especially the subject of construction cost estimation. So there needs to be an effort that can provide students' readiness to learn about the material to be discussed, namely by providing a videoscribe. The purpose of this study is to find out how effective the provision of videoscribe is for the learning readiness of class XI students in the subject of construction cost estimation at SMK PU Negeri Bandung. This type of research is an experimental research using a pre-experimental method with a one shot case study research design. The sample of this research was 72 students of class XI DPIB SMK PU Negeri Bandung. While the data collection technique used is a learning readiness test. Based on the results of the study, it is known that the effectiveness of providing videoscribe for learning readiness is 82,33%. This shows that the provision of a videoscribe for the learning readiness of class XI students in the subject of construction cost estimation at SMK PU Negeri Bandung is in the very effective category.